Associations between age-related macular degeneration, Alzheimer disease, and dementia: record linkage study of hospital admissions. - Keenan, T; Goldacre, R; Goldacre, M (2014)
IMPORTANCE: The potential association between age-related macular degeneration (AMD) and Alzheimer disease (AD) is uncertain and has implications for understanding disease pathogenesis, referral, and treatments. OBJECTIVES: To determine whether individuals admitted to the hospital with AMD were significantly more or less likely to develop AD or dementia in the following years, as well as to assess whether people with AD or dementia were significantly more or less likely to be admitted to the hospital for AMD treatment in the years following diagnosis of dementia. DESIGN, SETTING, AND PARTICIPANTS: An AMD cohort of 65,894 people was constructed from English National Health Service, linked hospital episode statistics from January 1, 1999, through February 28, 2011, by identifying computerized record abstracts for all people with an admission or day case care for AMD. A dementia cohort (168,092 people) and a reference cohort (>7.7 million people) were constructed in similar ways. MAIN OUTCOMES AND MEASURES: Risk of AD or dementia following AMD and risk of AMD following AD or dementia. Rate ratios were calculated based on standardized rates of AD and dementia in the AMD cohort, as well as standardized rates of AMD in the AD and dementia cohort, relative to those in the reference cohort. RESULTS The risk of AD or dementia following AMD was not elevated. The rate ratio was 0.86 (95% CI, 0.67-1.08) for AD and 0.91 (0.79-1.04) for dementia. The likelihood of being admitted for AMD following AD or dementia was very low: the rate ratio was 0.04 (0.01-0.10) for people with AD and 0.07 (0.04-0.11) for those with dementia. CONCLUSIONS AND RELEVANCE: These neurodegenerative conditions may share environmental risk factors and histopathologic features. However, considering AD and other dementia after AMD, their coexistence at the individual level is no different from that expected by chance. Our data also suggest that patients in England with dementia may be substantially less likely to receive AMD treatment. Further research is required to determine whether people with dementia receive appropriate investigation and treatment for AMD, as well as identify and address potential barriers.